Homoserine and quorum-sensing acyl homoserine lactones as alternative sources of threonine: A potential role for homoserine kinase in insect-stage Trypanosoma brucei - Mohamed Suhaimi N.-A. (Blackwell Publishing, 2016)
10.1111/mmi.12853